Chemo-botanical and Neurological Accounts of Some Ayurvedic Plants Useful in Mental Health - Balkrishna, Acharya; Misra, Laxminarain (Natural Products Journal, The, 2018)
Background: Now-a-days, herbal treatments are preferred over synthetic drugs for a range of human brain disorders including, Alzheimer's disease, Parkinson's disease, depression, epilepsy, schizophrenia, anxiety, etc. Ayurvedic system of medicine has traditionally been used in several neurological conditions. In general, much attention is drawn towards the established traditional systems of herbal remedies for many brain disorders, generating positive hopes for the patients. It is estimated that more than 60 million Indian population suffers from mental disorders. Results: Easy accessibility, negligible incidence of side effects and cost effectiveness of plant products offer considerable advantages. The Ayurvedic prescriptions have been proven to be very useful in mental health. The plant materials prescribed for these problems range from herbs to perennial trees with varied plant parts, ranging from whole plant, roots, stem, bark, leaves, flowers, fruits to seeds. A total of fifty six promising plants have been selected. The chemical structure of the major compounds from these plants range from straight chain fatty acids to terpenoids, steroids, flavonoids, alkaloids, peptides, etc. Conclusion: In the present paper, it has been attempted to review the botanical descriptions, Ayurvedic prescriptions, scientific validations and chemical compositions of the plants which have been in use as an ingredient of Ayurvedic medicine for mental health.
Keywords: chemical constituents